Perinatal exposure to germinated brown rice and its gamma amino-butyric acid-rich extract prevents high fat diet-induced insulin resistance in first generation rat offspring - Adamu, Hadiza Altine; Imam, Mustapha Umar; Ooi, Der-Jiun; Mohd Esa, Norhaizan; Rosli, Rozita; Ismail, Maznah (Taylor & Francis, 2016)
BACKGROUND:Evidence suggests perinatal environments influence the risk of developing insulin resistance. OBJECTIVE:The present study was aimed at determining the effects of intrauterine exposure to germinated brown rice (GBR) and GBR-derived gamma (γ) aminobutyric acid (GABA) extract on epigenetically mediated high fat diet-induced insulin resistance.DESIGN:Pregnant Sprague Dawley rats were fed high-fat diet (HFD), HFD+GBR, or HFD+GABA throughout pregnancy until 4 weeks postdelivery. The pups were weighed weekly and maintained on normal pellet until 8 weeks postdelivery. After sacrifice, biochemical markers of obesity and insulin resistance including oral glucose tolerance test, adiponectin, leptin, and retinol binding protein-4 (RBP4) were measured. Hepatic gene expression changes and the global methylation and histone acetylation levels were also evaluated. RESULTS:Detailed analyses revealed that mothers given GBR and GABA extract, and their offspring had increased adiponectin levels and reduced insulin, homeostasis model assessment of insulin resistance, leptin, oxidative stress, and RBP4 levels, while their hepatic mRNA levels of GLUT2 and IPF1 were increased. Furthermore, GBR and GABA extract lowered global DNA methylation levels and modulated H3 and H4 acetylation levels. CONCLUSIONS:These results showed that intrauterine exposure to GBR-influenced metabolic outcomes in offspring of rats with underlying epigenetic changes and transcriptional implications that led to improved glucose homeostasis.